Acetaldehyde accumulation in rat mammary tissue after an acute treatment with alcohol - Castro, Gerardo Daniel (2007)
Previous studies reported the presence in rat mammary tissue of a cytosolic xanthine oxidoreductase pathway for the metabolism of alcohol to acetaldehyde and hydroxyl radicals and to the microsomal biotransformation of ethanol to acetaldehyde. It was also reported that after chronic ethanol drinking stressful oxidative conditions can be observed. The present work reports that even after single doses of ethanol, given at three different levels (6.3 g kg(-1); 3.8 g kg(-1) or 0.6 g kg(-1) p.o.), acetaldehyde accumulates for prolonged periods of time in the mammary tissue to reach concentrations higher than in blood (e.g. 5.1 +/- 1.2 nmol g(-1) versus 0.2 +/- 0.1 nmol ml(-1), for 6.3 g kg(-1) dose, 6 h after intoxication). The presence in rat mammary tissue of low activities of additional enzymes able to generate acetaldehyde was established (alcohol dehydrogenase: 0.97 +/- 0.84 mU mg(-1) protein; CYP2E1: 1.30 +/- 0.12 x 10(-2) pmol 4-nitrocatechol min(-1) mg(-1) protein) and a low activity of aldehyde dehydrogenase was observed in the cytosolic, mitochondrial and microsomal fractions (0.02 +/- 0.04; 0.35 +/- 0.09 and 0.72 +/- 0.19 mU mg(-1) protein, respectively). After a single high dose of ethanol, an increased susceptibility to oxidative stress was observed, as evidenced by changes in the shape of t-butylhydroperoxide induced emission of chemiluminescence in mammary tissue (6.3 g kg(-1) dose; at 3 and 6 h). In summary, the results show that even after single doses of ethanol, acetaldehyde, either formed in situ or arriving via blood, tends to accumulate in mammary tissue and that this condition might decrease cell defenses against injury.